The Evolution and Application of Thematic Analysis in Language Services Research: Methodological Challenges, Reflections, and Future Directions - Tian, Xiaoming; Sun, Siyi; Xu, Lihua (Journal of Language Service Studies, 2026)
This article provides a critical examination of the evolution, application, and methodological implications of thematic analysis (TA) within language services research. Drawing on the principles of reflexive thematic analysis (RTA) as both an organizing and interpretive framework, the study reviews and synthesizes existing literature across six key domains: national language planning, urban governance, emergency language services, language economics, talent development and technological integration, and meta-level methodological mapping. Through this synthesis, the study identifies several recurring methodological challenges, including ambiguous epistemological positioning, limited interpretive depth, insufficient reflexivity, and low analytical transparency. Across these domains, TA demonstrates significant potential to illuminate both micro-level professional practices and macro-level structural dynamics. It enables researchers to uncover gaps in policy implementation, inequalities in resource allocation, and emerging tensions related to technological integration in language services. At the same time, the analysis reveals the need for greater methodological clarity and reflexive engagement in order to strengthen analytical validity. In response to these challenges, the article offers reflective insights and practical recommendations aimed at enhancing methodological rigor and conceptual innovation. The study concludes by outlining future directions for the field, including the integration of TA with emerging artificial intelligence tools, the refinement of analytic frameworks, and the advancement of theoretical, methodological, and ethical robustness in language services research.